Descriptive analysis of eco-fashion practices in footwear production of selected shoe manufacturers - Cainila, Lalaine Ann M. (College of Home Economics, University of the Philippines Diliman, 2010)
ABSTRACT This study is a descriptive form of research which attempted to identify the eco-fashion practices of three footwear manufacturers in Marikina. It aimed to attain the following objectives: (1) to identify eco-fashion concepts and practices in footwear manufacturing, (2) to determine footwear production and processes in selected shoe manufacturers in Marikina, (3) to identify eco-fashion awareness and practices employed by these companies, (4) to determine the key issues concerning ethical and environment practices and (5) to identify government regulations and actions to promote eco-fashion in the footwear industry